Associations of sympathetic and parasympathetic activity in job stress and burnout: A systematic review - de Looff, P. C.; Cornet, L. J. M.; Embregts, P. J. C. M.; Nijman, H. L. I.; Didden, H. C. M. (PLOS ONE, 2018)
This systematic review examines the relationship between sympathetic and parasympathetic activity on the one hand and job stress and burnout on the other, and is registered at PROSPERO under CRD42016035918. Background: Previous research has shown that prolonged job stress may lead to burnout, and that differences in heart rate variability are apparent in people who have heightened job stress. Aims: In this systematic review, the associations between job stress or burnout and heart rate (variability) or skin conductance are studied. Besides, it was investigated which–if any–guidelines are available for ambulatory assessment and reporting of the results. Methods: We extracted data from relevant databases following the PRESS checklist and contacted authors for additional resources. Participants included the employed adult population comparing validated job stress and burnout questionnaires examining heart rate and electrodermal activity. Synthesis followed the PRISMA guidelines of reporting systematic reviews. Results: The results showed a positive association between job stress and heart rate, and a negative association between job stress and heart rate variability measures. No definite conclusion could be drawn with regard to burnout and psychophysiological measures. No studies on electrodermal activity could be included based on the inclusion criteria. Conclusions: High levels of job stress are associated with an increased heart rate, and decreased heart rate variability measures. Recommendations for ambulatory assessment and reporting (STROBE) are discussed in light of the findings.